Dstyk mutation leads to congenital scoliosis-like vertebral malformations in zebrafish via dysregulated mTORC1/TFEB pathway - Xianding Sun; Yang Zhou; Ruobin Zhang; Zuqiang Wang; Meng Xu; Dali Zhang; Junlan Huang; Fengtao Luo; Fangfang Li; Zhenhong Ni; Siru Zhou; Hangang Chen; et al. (2020)
Abstract Congenital scoliosis (CS) is a complex genetic disorder characterized by vertebral malformations. The precise etiology of CS is not fully defined. Here, we identify that mutation in dual serine/threonine and tyrosine protein kinase ( dstyk ) lead to CS-like vertebral malformations in zebrafish. We demonstrate that the scoliosis in dstyk mutants is related to the wavy and malformed notochord sheath formation and abnormal axial skeleton segmentation due to dysregulated biogenesis of notochord vacuoles and notochord function. Further studies show that DSTYK is located in late endosomal/lysosomal compartments and is involved in the lysosome biogenesis in mammalian cells. Dstyk knockdown inhibits notochord vacuole and lysosome biogenesis through mTORC1-dependent repression of TFEB nuclear translocation. Inhibition of mTORC1 activity can rescue the defect in notochord vacuole biogenesis and scoliosis in dstyk mutants. Together, our findings reveal a key role of DSTYK in notochord vacuole biogenesis, notochord morphogenesis and spine development through mTORC1/TFEB pathway.